Wybrane aspekty probacyjnego naprawienia szkody wyrządzonej przestępstwem - Muszyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Obligation of remedying harm appears in the Penal Code in two different forms; as an unaided penal measure and as a probative measure associated with the institution of conditional extinction/redemption of criminal proceedings, conditional suspension of execution of the sentence, restriction of liberty. This article contains an assessment of legal regulations concerning probative remedying of harm resulting from crime. After discussing the presumptions of remedying ruling as a probative measure, the author shows the selected aspects concerning the ruling issues. She introduces a separate place for this measure in the system of legal and penal reaction to crime. The article also attempts to answer the question: What is the actual function of probative remedying of harm resulting from crime?
Keywords: naprawienie szkody; środki dowodowe; probacja (prawo); przestępstwo